Is outpatient hysteroscopy accurate for the diagnosis of endometrial pathology among perimenopausal and postmenopausal women?. Issue 2 (February 2018) - Bar-On, Shikma; Ben-David, Alon; Rattan, Gilad; Grisaru, Dan
Abstract: Objective: To assess the histological and visual accuracy of outpatient hysteroscopy. Methods: This was a retrospective analysis of all women referred to a tertiary center outpatient hysteroscopy clinic between March 2011 and October 2016 for the following indications: postmenopausal bleeding, suspected polyp, and/or thick endometrium. Histological accuracy was evaluated by comparing specimens obtained in hysteroscopy with those obtained by hysterectomy, and visual accuracy was evaluated by comparing visual findings with those obtained by biopsies. Sensitivity, specificity, positive predictive value, negative predictive value, and likelihood ratio were calculated to assess visual accuracy. Results: The mean age of participants was 54.14 (interquartile range 43.0-64.0). A total of 408 pathological specimens were obtained from outpatient hysteroscopies during the 712 visits recorded in the clinic log. Histological accuracy was evaluated in 15 participants who eventually underwent hysterectomy. Total percent of agreement between hysteroscopy biopsies and final pathology obtained by hysterectomy was 73% (kappa = 0.47). Overall visual accuracy was calculated with a 93.1% sensitivity, 52.1% specificity, 90.4% positive predictive value, and 61.0% negative predictive value. Visual accuracy for benign pathology was generally higher compared with that for pre and malignant lesions. Visual accuracy was satisfactory for the diagnosis of endometrial carcinoma with sensitivity and specificity of 71.4% and 98.9%, respectively, but poor for diagnosing hyperplasia with sensitivity and specificity of 25.0% and 96.6%, respectively. Conclusions: Outpatient hysteroscopy is an adequate and reliable tool for the evaluation of benign pathology in the uterine cavity. Visual findings may not suffice, and directed biopsies may be required to improve diagnostic accuracy.